KUANTITAS ASET BANK SYARIAH DI INDONESIA - Roikhan Mochamad Aziz; Fahrudin Fahrudin (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2021)
This study aims to analyze the influence of Islamic banking financing, certificates of Indonesia sharia banks, and third-party funds, short-term and longterm to total assets of the Islamic banking in Indonesia. Analyses were performed using monthly time series data published by Bank Indonesia from 2006 to 2011 The method used in this study is the dynamic model of Engle and Granger, Error Correction Model.The results of this study indicate that Islamic banking financing variables (0.0000), Bank Indonesia Sharia Certificate (0.0001) and third-party funds (0.0000) has a positive and significant impact in the short term to total assets of the Islamic banking in Indonesia, as well as in the long-term variable Islamic banking financing (0.0297), bank Indonesia sharia certificate (0.0011) and thirdparty funds (0.0299) also has a positive and significant impact on the total assets of the Islamic banking in Indonesia.